Theoretical Proposal for an Integrated Sustainability Performance Measurement System in the Supply Chain - Santos, Davidson de Almeida; Quelhas, Osvaldo Luiz Gonçalves; Gomes, Carlos Francisco Simões; Filho, José Rodrigues de Farias (Frontiers in Sustainability, 2021)
Environmental impacts due to supply chains are seen as a challenge to innovation and criteria for prioritizing the application of organizational resources. In this context, the research question arises: how to build the necessary knowledge about supply chain performance indicators in sustainability, systematizing in an evaluation process integrated with the organizational results? The general objective of this research is to build an integrated system of sustainability performance analysis of the supply chain. In order to achieve the general objective, the specific objectives are the following: (i) selection of the bibliographic portfolio and (ii) analysis of articles content. The exploratory-descriptive research method presents and illustrates a structured process for the selection of scientific articles on supply chain performance indicators in the sustainability context. The method identified the most important keywords and the main databases of full texts and abstracts aligned with the topic. An important review of the literature reveals that efforts to improve or influence the practice of sustainability in the supply chain raise critical questions about the transaction costs and effectiveness of the approach. The review promoted the development of a system of indicators inspired by the Balanced ScorCard (BSC) to address sustainability performance issues. The originality or value lies on the useful for managers throughout the supply chain. It was identified in the literature that supply chains still generate significant environmental impacts, social impacts, and use of natural resources, even though they individually present statements in their strategies and accountability indicating the priority regarding the mitigation of social, environmental, and economic impacts. Another finding is that it is not just a matter of complying with legal and institutional frameworks. The scientific literature defines the need to prioritize studies on Green Supply Chain Management (GSCM), which helps organizations in the production chain to achieve competitiveness and at the same time emphasize the reduction of social risks and environmental impacts. The main findings of the paper are related to the possibility of interfacing the dimensions present in TBL with performance measurement in a supply chain.